P3.160 Optimising existing sexual health clinics increases hiv testing among gay and bisexual men at higher risk of infection. (8th July 2017) - Jamil, Muhammad Shahid; Mcmanus, Hamish; Callander, Denton; Prestage, Garrett; Ali, Hammad; Knight, Vickie; Duck, Tim; O'connor, Catherine C; Chen, Marcus; Mcnulty, Anna M; Keen, Phillip; Medland, Nick; et al.
Abstract : Introduction: Globally, community-based HIV testing models are recommended to improve access to testing with less focus on optimising existing clinical services. In the past 5 years, public-funded sexual health clinics (SHCs) in New South Wales (NSW, Australia) have taken a range of initiatives to improve efficiencies such as triage to divert low-risk heterosexuals, express clinics, online booking, self-registration and SMS reminders. We analysed temporal trends in HIV testing among gay and bisexual men (GBM) attending SHCs in this period and assessed if testing was targeted to high-risk GBM. Methods: We used retrospective data from 32 SHCs in NSW participating in a surveillance network. HIV-negative GBM were categorised based on client type (new or existing), risk status (using partner numbers and/or recent rectal sexually transmitted infection), and recent HIV testing (past 6 months for high-risk, past 12 months for low-risk GBM). We used repeated measures Poisson regression to assess trends in attendance, tests and contribution to total tests by GBM categories. Results: From 2009–2015, unique GBM attending increased by 82% (5, 477 to 9, 983), and HIV tests increased by 155% (4, 779 to 12, 173) with significant increase in all categories and greatest increase in existing high-risk clients. Of 58, 377 HIV tests done, 74% were in existing and 35% in high-risk clients. Over time, existing high-risk clients with recent testing had an increasingly larger contribution to total tests (13% annual increase, 95% CI:8%–18%, p<0.001). There was a simultaneous annual decline in contribution by these low-risk categories: new clients (5% decline, 95% CI:2%–7%, p<0.001); existing clients with no recent testing (6% decline, 95% CI:5%–7%, p<0.001). There were no changes in contribution by other categories (new high-risk clients; existing high-risk clients with no recent testing; existing low-risk clients with recent testing). Conclusion: SHCs in NSW have successfully increased HIV testing among GBM, with greatest increase in high-risk men. The strategies adopted could be translated to other settings.